2009
DOI: 10.1007/s10151-009-0501-7
|View full text |Cite
|
Sign up to set email alerts
|

Young-age onset of colorectal cancer in Israel

Abstract: Younger age of onset colorectal cancer in our cohort of Israeli patients is associated with higher percentage of Arab patients, mucinous cancers, female gender, and advanced stage at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
11
1
1
Order By: Relevance
“…Similar studies in Jordan and Israel showed a predominant proportion of female in patients with early-onset CRC (Al-Jaberi et al, 2003;Neufeld et al, 2009). This could be explained partly by the racial and enviromental differences.…”
Section: Discussionmentioning
confidence: 56%
“…Similar studies in Jordan and Israel showed a predominant proportion of female in patients with early-onset CRC (Al-Jaberi et al, 2003;Neufeld et al, 2009). This could be explained partly by the racial and enviromental differences.…”
Section: Discussionmentioning
confidence: 56%
“…Many studies evaluated biological behavior and risk of relapse and death in young patients with CC [3], [4], [5], [7], [8], [9], [10], [11]. Despite much research, CC in the young has not been well characterized, due to conflicting data in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistent could be explained by: First, the current definition of young CRC patients remains controversial. Although majority of studies in the literature used the cutoff age of 40 years to denote a young patients with CC [3], [4], [5], [6], [7], some other studies used the cutoff age of 30 years [4], [15], 25 years [16] or others [17], [18], [19]. Second, young age consisted wide age range of population, which maybe an inherent characteristic of heterogeneous, different composition of young subgroup may cause different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In younger patients, there seems to be a higher frequency of tumors with poor differentiation, T4 disease stage, and vascular invasion. 7,8 A recent retrospective review of nine phase III chemotherapy trials in patients with advanced CRC assessed outcomes in younger versus older patients, as defined by age < 40 or > 50 years. 9 Although younger age was associated with shorter progression-free survival (PFS), there was no difference in overall survival (OS) or response rates for younger versus older patients, and younger patients derived similar benefit from combination chemotherapy.…”
Section: Introductionmentioning
confidence: 99%